2021
DOI: 10.1007/s11218-021-09668-1
|View full text |Cite
|
Sign up to set email alerts
|

‘Believe in me, and I will too’: a study of how teachers’ expectations instilled confidence in Grade 10 students

Abstract: Teacher expectation research has continued to establish an association between what teachers expect of their students and what students accomplish academically. These expectations affect students when they are communicated by teachers through differential treatment in the class, but no qualitative research has sought adolescent students’ points of view about how they experience teacher expectation effects. This paper presents new research findings that explain how Grade 10 students experienced their teachers’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…On the other hand, (Johnston, 2021) have studied learning professional confidence, linking teaching practices, students' self-perceptions, and gender. They have found that teaching practices are an influencing factor for students' self-confidence rather than students' background characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, (Johnston, 2021) have studied learning professional confidence, linking teaching practices, students' self-perceptions, and gender. They have found that teaching practices are an influencing factor for students' self-confidence rather than students' background characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…First, structure your classrooms using preventive strategies and interventions (i.e., Tier 1 strategies) for classroom and behavior management. This includes structuring activities to encourage high levels of student engagement (e.g., collaborative learning groups, Think-Pair-Share, equity sticks); maintaining high levels of expectations (e.g., believe in students, hold them accountable for assignments and behavior expectations); strong levels of teacher–student rapport (e.g., calling students by name, embracing diversity, creating and enforcing classroom community norms, small group work); modeling positive behaviors; and incorporating special interests in activities (e.g., favorite animals, sports, and culture; Johnson et al, 2021). Wording classroom rules and directions concisely and positively can increase positive student behaviors (e.g., use “walk” instead of “don’t run,” Mundschenk et al, 2011).…”
Section: Steps To Navigating the Cycle Of Dysregulationmentioning
confidence: 99%